Bcl-x(L) regulates mitochondrial energetics by stabilizing the inner membrane potential - Chen,Y-B; Aon,MA; Hsu,Y-T; Soane,L; Teng,X; McCaffery,JM; Cheng,W-C; Qi,B; Li,H; Alavian,KN; Dayhoff-Brannigan,M; Zou,S; et al. (The Journal of Cell Biology, 2011)
Mammalian Bcl-xL protein localizes to the outer mitochondrial membrane, where it inhibits apoptosis by binding Bax and inhibiting Bax-induced outer membrane permeabilization. Contrary to expectation, we found by electron microscopy and biochemical approaches that endogenous Bcl-xL also localized to inner mitochondrial cristae. Two-photon microscopy of cultured neurons revealed large fluctuations in inner mitochondrial membrane potential when Bcl-xL was genetically deleted or pharmacologically inhibited, indicating increased total ion flux into and out of mitochondria. Computational, biochemical, and genetic evidence indicated that Bcl-xL reduces futile ion flux across the inner mitochondrial membrane to prevent a wasteful drain on cellular resources, thereby preventing an energetic crisis during stress. Given that F1FO–ATP synthase directly affects mitochondrial membrane potential and having identified the mitochondrial ATP synthase β subunit in a screen for Bcl-xL–binding partners, we tested and found that Bcl-xL failed to protect β subunit–deficient yeast. Thus, by bolstering mitochondrial energetic capacity, Bcl-xL may contribute importantly to cell survival independently of other Bcl-2 family proteins.